As tecnologias de informação e comunicação nas escolas públicas de ensino médio do estado de São Paulo: políticas e ações - Flygare, Ivany Theodósio Lérco (2009)
This research had as objective to identify and to study the management actions, releted to institutionalized practices institutionalized practices from public policies of new educational technologies insertion implanted and implemented by the São Paulo State Educational Department, during the last decade, for schools offer just the high school of Diretoria de Ensino Região Leste 5 – Leste 5 Department of Education. This is a bibliographic and qualitative research because it answers an investigative question, that act in public school, ensuring the access to relevant informations, making possible some informative conclusions about a research trouble. The authors Kenski (2001), Levy (1993), Almeida (2006), Valente (2008), Moran, Masseto and Behrens (2000) assisted theoretically based on analysis. It assumed, at school, the technology could help the change in relationship between teachers and students, encouraging new knowledge process, projects development and, also, to support the new abilities development and the capacity analysis and problems solution. The results of the analysis and interpretation realized were so discovered and showed the convergence points, in the sense of to join the themes in either category adopted in this effort of interpretation from Advances and Obstacles categories insertion of new educational technologies of public policies in high school of São Paulo State Educational Department and the public policies developed in this direction. The results point for a relevant distance between which is proposed in the public policies and which is realized at schools.